P759 Incidence and clinical impact of perianal disease in patients with ulcerative colitis: a nationwide population-based study. (25th January 2019) - Song, E M; Lee, H-S; Kim, Y-J; Oh, E H; Ham, N S; Kim, J; Hwang, S W; Park, S H; Yang, D-H; Ye, B D; Byeon, J-S; Myung, S-J; et al.
Abstract: Background: The risk and clinical impact of perianal disease (PAD) in ulcerative colitis (UC) patients have not been fully evaluated. We investigated the incidence of PAD in UC patients and compared clinical characteristics and outcomes of UC according to the presence of PAD. Methods: We performed a nationwide population-based cohort study and a hospital-based cohort study. Using the 2010–2014 data from the Korean national health insurance claims database, we calculated incidence rates and standardised incidence ratios (SIRs) of PAD in UC patients compared with the general population. We evaluated the clinical characteristics and outcomes of UC patients with PAD in both population-based and hospital-based cohorts. To reduce clinically meaningful confounding factors, we also conducted matched analyses. Results: In the population-based cohort, the incidence rate and SIR of PAD in UC patients were 3.74/1000 person-years (95% confidence interval [CI], 3.25–4.31) and 2.88 (95% CI, 2.50–3.32), respectively. In the hospital-based cohort, the cumulative probabilities of PAD at 1, 5, 10, and 20 years after diagnosis were 1.0%, 2.3%, 4.0%, and 6.3%, respectively. In both population-based and hospital-based cohorts, UC patients with PAD showed higher proportions of corticosteroid use and extensive colitis at diagnosis. The requirements for anti-tumour necrosis factor agents and colectomy were significantly higher in UC patients with PAD before and after matched analysis. Conclusions: The risk of PAD is higher in UC patients than in the general population. UC patients with PAD have distinct clinical features and poor outcomes, as indicated by the greater need for UC-related medications and colectomy.